Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1371/journal.pntd.0005684
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive and angiogenic cytokine profile associated with Bartonella bacilliformis infection in post-outbreak and endemic areas of Carrion's disease in Peru

Abstract: Analysis of immune responses in Bartonella bacilliformis carriers are needed to understand acquisition of immunity to Carrion’s disease and may allow identifying biomarkers associated with bacterial infection and disease phases. Serum samples from 144 healthy subjects from 5 villages in the North of Peru collected in 2014 were analyzed. Four villages had a Carrion’s disease outbreak in 2013, and the other is a traditionally endemic area. Thirty cytokines, chemokines and growth factors were determined in sera b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…The transient depression of the cellular immunity that occurs during the acute hematic phase is of note (200), with patients presenting lymphopenia with a decrease in CD4 ϩ and a slight increase of CD8 ϩ T lymphocytes. Recent data support the possibility that this immunosuppression remains long after the end of the acute phase (190). These findings may reflect an immune tolerance (lack of a specific immune response to an antigen) which might be triggered by B. bacilliformis, leading to an immune evasion and installation of persistent bacteremia.…”
Section: Immunologymentioning
confidence: 85%
See 3 more Smart Citations
“…The transient depression of the cellular immunity that occurs during the acute hematic phase is of note (200), with patients presenting lymphopenia with a decrease in CD4 ϩ and a slight increase of CD8 ϩ T lymphocytes. Recent data support the possibility that this immunosuppression remains long after the end of the acute phase (190). These findings may reflect an immune tolerance (lack of a specific immune response to an antigen) which might be triggered by B. bacilliformis, leading to an immune evasion and installation of persistent bacteremia.…”
Section: Immunologymentioning
confidence: 85%
“…Significantly elevated IFN-␥ and IL-4 levels were reported in 21 patients in the chronic phase of the disease (187). Interestingly, for healthy preexposed and asymptomatic carriers it was observed that those having elevated IgG levels were more prone to have high eotaxin levels (P ϭ 0.006), while IgG seropositivity was correlated with VEGF levels (P ϭ 0.047), both of which are involved in angiogenic processes (190).…”
Section: Immunologymentioning
confidence: 97%
See 2 more Smart Citations
“…In vitro, B. henselae induces angiogenesis and proliferation of endothelial cells in part by stimulating production of VEGF. [23][24][25]31,53,54] It is well established that Bartonella spp. cause the non-neoplastic endothelial proliferative disorders bacillary angiomatosis and peliosis hepatis in humans, and there have also been rare reports of these conditions in dogs infected with Bartonella spp.…”
Section: Discussionmentioning
confidence: 99%